DRTA Strategy: An Effective Strategy for Teaching Reading - Innaya Dewi; Zahfatut Tarbiyah; Adenan Damiri (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2019)
The study's goal was to use the Directed Reading Thinking Activity (DRTA) technique to improve students' reading comprehension. This study aims to see if Directed Reading Thinking Activity (DRTA) enhances students' reading comprehension and if the average score of students' reading comprehension taught through DRTA is higher than that taught through solo reading. This study was carried out utilizing Classroom Action Research as a method. Kemmis and Taggart proposed a research paradigm that comprised two cycles: planning, action, observation, and reflection. Before beginning the cycle, the writer conducted a pre-cycle to assess students' reading comprehension. The writer and the English teacher collected student data for the study. The data was collected through field notes, observation sheets, and tests. The research was focused on increasing students learning activities and students reading comprehension. The average score in the pre-cycle result showed that pupils' reading comprehension had improved, with a score of 59,35. Only thirteen students, or 48.14% of the class, received a score higher than the Minimum Mastery Criterion. The outcome of Cycle 1 was 59,16, with eleven students or 59.25% scoring over the Minimum Mastery Threshold and ten students or 40.74% scoring below the criterion. The mean score for cycle 2 was 72.87, with twenty-three students or 85.18% participating. Four students, 14.81%, received a score above the Minimum Mastery Threshold, while the remaining four, 14.81%, received a score below the criterion. Classroom Action Research could be concluded after evaluating data and completing semantic mapping. Students learning activities and reading comprehension improved due to the reading method.